Ex Vivo Modeling of Human Neuroendocrine Tumors in Tissue Surrogates - Herring, Brendon; Jang, Samuel; Whitt, Jason; Goliwas, Kayla; Aburjania, Zviadi; Dudeja, Vikas; Ren, Bin; Berry, Joel; Bibb, James; Frost, Andra; Chen, Herbert; Rose, John Bart; et al. (Frontiers in Endocrinology, 2021)
Few models exist for studying neuroendocrine tumors (NETs), and there are mounting concerns that the currently available array of cell lines is not representative of NET biology. The lack of stable patient-derived NET xenograft models further limits the scientific community’s ability to make conclusions about NETs and their response to therapy in patients. To address these limitations, we propose the use of an ex vivo 3D flow-perfusion bioreactor system for culturing and studying patient-derived NET surrogates. Herein, we demonstrate the utility of the bioreactor system for culturing NET surrogates and provide methods for evaluating the efficacy of therapeutic agents on human NET cell line xenograft constructs and patient-derived NET surrogates. We also demonstrate that patient-derived NET tissues can be propagated using the bioreactor system and investigate the near-infrared (NIR) dye IR-783 for its use in monitoring their status within the bioreactor. The results indicate that the bioreactor system and similar 3D culture models may be valuable tools for culturing patient-derived NETs and monitoring their response to therapy ex vivo.